Red cell distribution width as a prognostic marker in septic neonates versus healthy term newborns - Sarma, Saran; George, Madhu; Tawab, Abdul; Zacharias, Ann Mary (International Journal of Contemporary Pediatrics, 2021)
Background: We evaluated the usefulness of RDW (red cell distribution width) as a diagnostic tool in newborn sepsis. Several biomarkers for sepsis have been studied including CRP (C-reactive protein), procalcitonin, interleukins, total WBC count (TC) absolute neutrophil count (ANC), ratio of immature neutrophils to total neutrophils (I/T ratio). An ideal biomarker for sepsis is still elusive. Hence we evaluated RDW as a sepsis marker as it was cheap and available. The objective of the study was to evaluate the role of RDW as a prognostic marker in newborn sepsis compared to healthy newborns. Methods: The study sample comprised of two groups (cases and control group) each with 40 neonates. Group 1 (cases group) comprised 40 newborns with suspected/probable sepsis based on clinical or laboratory parameters. In group 1 (suspected/probable sepsis) RDW was done at the time of suspicion of sepsis along with other relevant investigations. According to the clinical course these parameters were repeated 24-48 hrs after first value. Group 2 (control group) comprised 40 normal newborns in the postnatal ward. For the control group blood sampling for CBC and RDW was done simultaneously along with blood sampling for newborn screening. Results: On comparing the baseline variables there is no significant difference among cases and control group with respect to gender distribution, age in days, gestational age in weeks and birth weight. The mean RDW among the cases group was significantly higher than among the control group. In ROC analysis we obtained a cut off value of RDW of 17.25 is helpful to diagnose sepsis with reasonable sensitivity (70%) and specificity (60%). Conclusions: This study revealed that RDW may also be included in the diagnosis of sepsis in newborns as it is a simple, inexpensive, available and easily repeated test as it is routinely done with a complete blood count.